Lactate flux dysfunction in patients with bipolar disorder: preliminary insights from ultra-high field 7T MRSI during task and rest - Bertocci, Michele A.; Diler, Rasim S. (Frontiers in Neuroscience, 2025)
IntroductionThe symptoms of bipolar disorder (BD) may be characterized as disruptions in energy metabolism, and neural energy availability may serve as a mechanistic marker of BD. Lactate, the end product of glycolysis, is a poorly understood neural energy source that may contribute to the neural dysfunction underlying BD.MethodsWe aimed to assess precuneus lactate availability during an emotion processing task and during rest in a sample of participants with well-characterized, pediatric-onset BD (n = 17) and healthy participants (n = 8), using 7-Tesla (7T) magnetic resonance spectroscopic imaging (MRSI). The mean age of the participants was 19.2 years (3.8).ResultsIn this small sample, we observed that the difference in precuneus lactate availability between the emotion processing task and rest (e.g., lactate flux) was greater in participants with BD [mean = 0.014 (0.041)] than in healthy controls (HCs) [mean = −0.033 (0.028), t(17) = 2.64, p = 0.017, Cohen’s d = 1.3, Bayes factor10 = 3.528]. In addition, we found that this greater difference in lactate availability (task–rest) in participants with BD, particularly those with lower precuneus lactate availability at rest, demonstrated a trend related to elevated depression scores (r = 0.459, p = 0.055, Bayes factor10 = 1.617).DiscussionThese results suggest, for the first time, using ultra-high-field strength MRSI with a high signal-to-noise ratio, that lactate flux is dysfunctional in well-characterized BD. Our findings highlight the importance of lactate as a mechanistic marker of BD, which may be used to develop novel treatment options.